PENERAPAN DATA MINING DALAM PENENTUAN JURUSAN SISWA DENGAN METODE KLASIFIKASI ALGORITMA C4.5 STUDI KASUS SMAN 1 LEUWISADENG - Wendy Asswan Cahyadi; Deni Muharam; Samsuri Yahya (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2026)
The majoring of students in Senior High Schools (SMA) in the 2013 Curriculum is carried out when new students enter class Often students experience confusion in choosing subjects, due to students' lack of understanding of the subjects they will take. To overcome this, SMAN 1 Leuwisadeng opened direct consultations with BP/BK teachers to provide direction in choosing majors according to students' interests and abilities. However, the major system at SMAN 1 Leuwisadeng is still done manually. As technology develops, this can be overcome with data grouping techniques obtained from data mining results. Data mining is an activity that includes collecting, using data, history to find regularities, patterns or relationships in large data sets [1]. In this research, researchers used the C4.5 algorithm to predict students in determining the direction they would take. The accuracy results obtained in this program were 92.31%. Thus it can be concluded that data mining using the C4.5 Algorithm classification method can speed up the process for all students.